2013
DOI: 10.1051/0004-6361/201321721
|View full text |Cite
|
Sign up to set email alerts
|

Long-term multiwavelength studies of high-redshift blazar 0836+710

Abstract: Aims. The observation of γ-ray flares from blazar 0836+710 in 2011, following a period of quiescence, offered an opportunity to study correlated activity at different wavelengths for a high-redshift (z=2.218) active galactic nucleus. Methods. Optical and radio monitoring, plus Fermi-LAT γ-ray monitoring provided 2008-2012 coverage, while Swift offered auxiliary optical, ultraviolet, and X-ray information. Other contemporaneous observations were used to construct a broad-band spectral energy distribution.Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
3
27
1
Order By: Relevance
“…From the absence of a hot-spot in the arcsecond jet radio structure Perucho et al (2012a) concluded that the jet likely loses collimation and gets disrupted by the growth of helical instabilities. Akyuz et al (2013) analysed the multifrequency behaviour of the source during both a quiescent state in 2008-2011 and an active state in 2011. They found that the γ-ray emission correlates with the optical, but not with the radio emission and that the γ-ray spectrum becomes curved in active states.…”
Section: Introductionmentioning
confidence: 99%
“…From the absence of a hot-spot in the arcsecond jet radio structure Perucho et al (2012a) concluded that the jet likely loses collimation and gets disrupted by the growth of helical instabilities. Akyuz et al (2013) analysed the multifrequency behaviour of the source during both a quiescent state in 2008-2011 and an active state in 2011. They found that the γ-ray emission correlates with the optical, but not with the radio emission and that the γ-ray spectrum becomes curved in active states.…”
Section: Introductionmentioning
confidence: 99%
“…The γ-ray aca e-mail: jorstad@bu.edu 1 http://www.bu.edu/blazars/VLBAproject.html tivity lasted for a year, culminating on November 1st, 2011 when the γ-ray flux reached a maximum of S γ = (2.9 ± 0.4) × 10 −6 phot s −1 cm −2 at E>100 MeV, which corresponds to a luminosity of (1.1 ± 0.2) × 10 49 erg s −1 (H • =71 km s −1 Mpc −1 , Ω m =0.27, Ω Λ =0.73). The multifrequency behavior of 0836+71 during the γ-ray-outburst has been discussed by Akyuz et al [7]. These authors find a significant change of the shape of the γ-ray spectrum from straight to curved in the log S ν -logν plane, evidence for a positive correlation between γ-ray and optical flaring emission, and no clear correlation between γ-ray and radio variations.…”
Section: Introductionmentioning
confidence: 91%
“…The radio light curves at short wavelengths (≤8 mm) show an outburst that started ∼1.5 yr earlier than the γ-ray event (Figure 1). Although there is activity at mm wavelengths during the γ-ray outburst and the flux at 15 GHz reaches a maximum in the form of a plateau with a duration of several months that peaks at the maximum of the γ-ray outburst, the connection between γ-ray and radio light curves is not clear, as discussed by Akyuz et al [7].…”
Section: Variability At Different Wavelengthsmentioning
confidence: 98%
See 1 more Smart Citation
“…Between 2008 August and 2011 January the source was in a relatively quiescent state, although regularly detected on weekly time scales, with an average flux of about 5.2 × 10 −8 ph·cm −2 ·s −1 and a spectrum well represented by a power law with Γ γ ∼ 2.9. In 2011 March, S5 0836+710 entered in a high activity phase with multiple sub-flares, which lasted almost 11 months [16]. During the flaring period the spectrum changed shape deviating from a power law and showing a significant curvature.…”
Section: S5 0836+710mentioning
confidence: 99%